(untitled) (Acta Scientiarum. Biological Sciences, 2012)
Random amplified polymorphic DNA (RAPD) markers were used to investigate the genetic relationship among nests of the carpenter ant, Camponotus rufipes, located in the same area. Five random oligodecamers were used to amplify DNA from 108 ant workers collected from six nests. A total of 47 RAPD markers were identified, which revealed low levels of genetic differentiation among nests (Fst = 0.00218) and a low average Shannon index (0.3727) among workers within nests. These results together suggest that the C. rufipes nest may be formed by a single, once-mated queen and that nests produced by queens that are genetically related tend to keep their nests in close proximity to one other.